2005
DOI: 10.1007/s11661-005-0017-3
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural characterization of a modified 706-type Ni-Fe superalloy by small-angle neutron scattering and electron microscopy

Abstract: The new Ni-Fe-based superalloy DT706, derived from INCONEL 706, is the object of studies for potential uses in turbine-disk applications at temperatures above 973 K. This alloy aims at improving the microstructural stability while preserving the excellent machinability and good mechanical properties of the base material. This article is the first of a two-part study concentrating on the characterization of the microstructure of the DT706 precipitates, depending on the heat-treatment conditions. Analyses were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The precise measurement of precipitate volume fraction requires the measurement of the integrated intensity, which is the integral from 0 to infinity of I AE q 2 (Eq. [7] above). Since the experimental measurement is always made over a limited q-range, a precise measurement is possible only if proper extrapolations are made both for the low-q and high-q regions.…”
Section: Available Range Of Scattering Vectorsmentioning
confidence: 93%
See 1 more Smart Citation
“…The precise measurement of precipitate volume fraction requires the measurement of the integrated intensity, which is the integral from 0 to infinity of I AE q 2 (Eq. [7] above). Since the experimental measurement is always made over a limited q-range, a precise measurement is possible only if proper extrapolations are made both for the low-q and high-q regions.…”
Section: Available Range Of Scattering Vectorsmentioning
confidence: 93%
“…In the direct method, a certain distribution function of the precipitates is assumed, the scattering of which can be calculated and fitted to the experimental data as a function of the parameters of this function. For instance, a log-normal size distribution of precipitates is often assumed in the literature, [6][7][8][9][10] the size and dispersion of which can be adjusted. Other distributions, or combinations of several distributions, can naturally be used as well.…”
Section: Introductionmentioning
confidence: 99%
“…Complementary in-situ and ex-situ small-angle neutron scattering (SANS) investigations were performed to get representative information from larger volumes about the temporal evolution of the γ precipitate phase. Previous studies demonstrated that two-phase superalloys can be successfully analyzed by SANS to investigate the microstructural evolution of the γ/γ microstructure during heat treatments [14][15][16][17][18]. In this study, the γ precipitate size distributions and volume fractions during the heat treatment procedures and after the full three-step heat treatment were determined quantitatively.…”
Section: Introductionmentioning
confidence: 98%
“…It is especially crucial to control the evolution of the different phases at high temperature in order to tailor the mechanical properties. [6][7][8][9] The aim of increasing the operation temperature of the Ni-based superalloys, which allows engine manufacturers to improve fuel efficiency and, thus, results in reduced emissions, forces the development of materials stable at higher temperatures. The last few decades the scientific community has put great effort into the development of Ni-based alloys with operation temperatures above 650°C while keeping the good processing C. SOLI´S, J. MUNKE, and R. GILLES are with the Heinz MaierLeibnitz Zentrum (MLZ), TU Mu¨nchen, Lichtenbergstr.…”
Section: Introductionmentioning
confidence: 99%